2012
DOI: 10.3109/0142159x.2012.644830
|View full text |Cite
|
Sign up to set email alerts
|

Distress and empathy do not drive changes in specialty preference among US medical students

Abstract: Background: Although medical student specialty choices shape the future of the healthcare workforce, factors influencing changes in specialty preference during training remain poorly understood. Aim: To explore if medical student distress and empathy predicts changes in students' specialty preference. Methods: A total of 858/1321 medical students attending five medical schools responded to surveys in 2006 and 2007. The survey included questions about specialty choice, burnout, depression, quality of life, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 58 publications
1
6
0
1
Order By: Relevance
“…The prevalence of depression among both medical and dental students was 67%, which is higher than all studies conducted outside Saudi Arabia. [6][7][8][9] When this result was compared with the Saudi study, we found it was also higher than two previous studies done in Riyadh and Jeddah, 15,17 but very similar to studies done in Qassim 16 and Makkah. 18 The Makkah study with a similar result for depression used the same measurement tool (DASS-21) to assess governmental university students in preclinical years, which is in contrast to our study involving four different educational bodies, both governmental and private, and which was conducted among students and interns in clinical years of study.…”
Section: Discussionsupporting
confidence: 75%
“…The prevalence of depression among both medical and dental students was 67%, which is higher than all studies conducted outside Saudi Arabia. [6][7][8][9] When this result was compared with the Saudi study, we found it was also higher than two previous studies done in Riyadh and Jeddah, 15,17 but very similar to studies done in Qassim 16 and Makkah. 18 The Makkah study with a similar result for depression used the same measurement tool (DASS-21) to assess governmental university students in preclinical years, which is in contrast to our study involving four different educational bodies, both governmental and private, and which was conducted among students and interns in clinical years of study.…”
Section: Discussionsupporting
confidence: 75%
“…To date, no study has linked the literatures on specialty choice (specific to lifestyle controllability and income) and burnout in medical students. One recent study examined associations between burnout and any change in specialty preference (primary care versus surgical versus non‐primary care/non‐surgical), as well as changes in preference away from primary care, among medical students over 1 year 30 . Results indicated that higher levels of depersonalisation‐related burnout predicted any change in specialty preference, but that no burnout variables predicted a change in choice away from primary care.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been done regarding the choices of specialty and factors influencing them in undergraduate medical students and junior doctors, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] who have less experience regarding the clinical exposure and, most of the times choices made are temporary and are liable to change as their medical education continues. 12 Similar result was seen in our study, among those who had specialty choice at the beginning of the MBBS, 52% has changed the specialty choice during the entrance of postgraduate study.…”
Section: Discussionmentioning
confidence: 99%